Bullying e ciberbullying: ações, programas e projetos de enfrentamento nas escolas públicas de Uberlândia - Carvalho Júnior, Gilson Roberto de Abreu (2014)
This research aimed to understand actions, projects and programs to combat bullying and cyberbullying in municipal and state public schools in Uberlândia and investigated the actions, projects and programs for this question. These phenomena of violence, that occur in the schools and in the social networks - which are referenced by the students themselves - are part of the reality of any large city and they are headlines of newspapers and other media. The clipping considered schools that offer Elementary II, school age from 11 to 14 years old, where there is a higher incidence of cases. The research showed the difference between school violence and such phenomena, their characteristics and potential consequences; run the history of how bullying and cyberbullying had become part of the scenery of Brazilian schools; investigated the effort to combat them. Data were collected from school professionals who had knowledge and contact with the dynamics of Elementary school II as education specialists. The techniques used were semi-structured interviews, analysis of documents and media, such as websites and blogs. Due to the fact that this research had an object of study still little applied in Uberlândia area, the emphasis is to offer it to the Department of Education and the Regional Superintendent of Education as reference to actions, projects and future programs for educators who deal daily, in highest or in lowest dimension, with the aggressor, the victims and the audience: actors involved in bullying and cyberbullying.